Analysis of the Influence of Discipline, Work Motivation, and Career Development on the Performance of Civil Servants at the Badan Pusat Statistik (BPS) of Provinsi Maluku Utara - Uli, Soraya Diana; Marwan, Marwan; Maharani, Anita (Budapest International Research and Critics University, 2025)
This study analyzes the influence of discipline, work motivation, and career development on the performance of civil servants at the Central Statistics Agency (BPS) of North Maluku Province. The results of the tests show that discipline (X1) and career development (X3) have a significant effect on performance (Y), while work motivation (X2) does not. The regression coefficient for discipline is positive (0.421), indicating that an increase in discipline directly impacts improved performance. Simultaneously, the three variables contribute 75.5% to performance, with the remaining influence being attributed to other factors. The adjusted R² value is used to ensure the accuracy of the model in measuring the effect of independent variables on performance. It is recommended that agency leaders continue to enhance discipline and provide career development opportunities for employees. Additionally, strategies to improve work motivation should be evaluated to have a more significant impact on performance. Management should prioritize the establishment of a consistent work discipline culture and provide clear and structured career development paths for civil servants. This is crucial to foster optimal performance and improve organizational effectiveness.